The influence of transportation, social norms, cultural identity, and affective disposition in transnational media enjoyment - Wang, Jing; Ye, Qiqi; Shuai, Zhiqiang; Wang, Peifeng; Wang, Yujie; Lin, Changqing (Frontiers in Psychology, 2024)
Background The globalization of the media market is forcing decision-makers to understand the psychological processes behind local audiences’ enjoyment of foreign TV dramas. Transportation is a well-established psychological theory and framework utilized to elucidate and anticipate audience engagement and enjoyment in the cognitive process of experiencing a narrative text. Although there is a substantial body of literature on transportation and media enjoyment, there is a noticeable absence of studies on the relationship between audiences being “transported” into the narrative world of TV dramas and, particularly, the pleasure audiences derive from interacting with media content within a cross-cultural acceptance context. Method The research employs a quantitative design, with responses collected from 353 students enrolled at a Malaysian public university. It aims to validate the influence of social norms, cultural identity, and affective disposition on narrative immersion while watching foreign TV dramas, as well as the subsequent enjoyment of media among local audiences. Results The results indicate that social norms, cultural identity, and affective disposition significantly influence transportation and enjoyment. Furthermore, the influence of cultural identity on social norms has a positive moderating effect on transportation. Discussion Storytelling that complies with social norms while offering new perspectives can maximally engage audiences, potentially altering their narrative cognition and deepening their immersion in fictional narratives. Cultural identity can shape audience perceptions and reactions to cross-cultural media consumption, ultimately influencing the degree to which audiences are drawn into the narrative. Furthermore, the audience’s emotional connection to characters in the narrative or to situations in the drama significantly influences the overall cognitive and immersion levels.